The intimacy effect: Girls’ reflections about pornography and ‘actual sex’ - Sanna Spišák (Sage, 2022)
Drawing on an online survey that was conducted as part of the media education awareness campaign of a Finnish online youth club, this article explores girls’ conceptions of the difference between pornographic representations and ‘actual sex’. As a result of the analysis, the greatest detachment between these two occurs concerning intimacy. Thus, this article will explore the pervasive influence of the notion of romantic intimacies, which provides the ideal for ‘normal’ relationships, sexual encounters and ‘good sex’ for the girls who participated in the survey through the concept of ‘the intimacy effect’. Like narratives of sexual storytelling in general, the survey dataset helps to trace connections between the personal and the societal. The dataset also draws attention to the ties between social relations and the cultural forms that mediate how these relations are set in motion, and to how certain cultural norms are forcefully influencing girls’ everyday life.